Os efeitos do aumento gradual da exposição a um ruído e do tempo de atraso em respostas autocontroladas e impulsivas em um esquema de escolhas concorrentes - Santos, Samara Fernanda dos (2018)
In a context of competing choices, in which one choice leads to a minor and immediate consequence, and another that leads to a greater but delayed consequence, the choice for the first can be called an impulsive choice, and the choice of the latter can be called self-controlled. Many studies have been carried out in order to specify the variables that make it more or less probable to choose between one alternative and another. However, some variables have been analyzed less frequently, such as aversive events. In the present work, the objective was to verify the effect of the gradual increase to the exposure to a noise and the increase of the delay time on answers in a scheme of competing choices. Five adult subjects of both genders participated in the study. Participants were exposed to an ABAB reversal design. The experimental task in a concurrent scheme, which presented two stimuli simultaneously to the participant, in which the choice in one of them was followed by a greater and delayed consequence (larger amount of hypothetical money), and the choice in the other was followed by a minor consequence and immediate (smaller amount of hypothetical money). There were four experimental conditions: baseline with gradual increase in delay time; noise; baseline with stabilized delay time; noise. Under these conditions the manipulated variables were the increase of the delay time and the increase of the time of exposure to the noise. The results showed that for the participants who reached criterion in the first condition, the manipulated aversive variable produced the expected effect, that is, the reversion of preference. For the other participants, the results were not conclusive, since not all reached criteria for the other conditions. Some aspects may have contributed to this result, for example, the sound properties of the selected noise, the use of the same noise for all the participants, the disproportion between time of delay and amount to be obtained, among others. Future studies need to establish more effective procedures to achieve more precise stability criteria that allow all participants to be exposed to all conditions.